ANALISIS KELAYAKAN REALISASI SATUANTEGANGAN LISTRIK DC STANDAR INTERNASIONAL UNTUK PUSLIT KIM-LIPI BERDASARKAN DEFINISI QUANTUM DENGAN KETELITIAN DIBAWAH 0,1 PPM - Hadi Sarjono (Badan Standardisasi Nasional, 2008)
Recently, there are two technical methodes for a realization of the international standard of dc voltage unit such as convertional Josephson Voltage Standards (JVS) and Programmable Josephson Voltage Standard (PJVS).